PENGAMBILAN KEPUTUSAN, SIKAP DAN KEPUASAN KONSUMEN TERHADAP PAKET NASI LIWET DI RMSASA BANDAR LAMPUNG - Erin Apriani; Yaktiworo Indriani; Rabiatul Adawiyah (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2021)
The study aims to know the decision making, attitude, and satisfaction of consumers towards steam rice package at The Sambel Alu Sultan Agung (RMSASA) Restaurant. The attributes studied consisted of price, scent, taste, size, benefit, side dish variation, dish appearance, cleanliness, location, parking area, comfort and safety place. This research was conducted by survey method.  The respondents of this study consisted of 48 consumers who purchased liwet rice package for the first time. The research data was analyzed by description, Fishbein Multi-attribute Model, Customer Satisfaction Index (CSI,) and Importance Performance Analysis (IPA).  The results showed that the consumer's decision-making process of purchasing steam rice package was influenced by consumers' desire to try liwet rice package besides their hunger.  Sources of information obtained by consumers were mostly from people stories.  Alternatives chosen by consumers when the liwet rice package ran out was switching to another menu. The calculation of attitude of consumers showed that consumers like the liwet rice package with multi-atribute value of 182.06.  The highest score of attitude was taste, followed by cleanliness, comfort and safety place.  The results of CSI analysis showed that consumers were satisfied with the liwet rice package with CSI value of 77.54.  Meanwhile, based on IPA analysis, the attributes laid in quadrant I were aroma and location; quadrant II were cleanliness, taste, comfort and safety place; quadrant III were parking areas, price, size, and benefit; and quadrant IV were menu variation and dish appearance. Key words: attitude, CSI, IPA, steam rice, the decision making